Effect of Promotional Mix on Credit Card Usage Decisions for Customers of PT BNI (Persero) Tbk Manado Area During the Covid-19 Pandemic - Soewarno, Lidya Endah Sugiarti; Tumbuan, Willem JF Alfa; Jan, Arrazi Hasan (Research Parks Publishers, 2022)
The payment system using a credit card is an effort to reduce the use of cash instruments, in addition to debit cards and electronic money. With current technological developments, payment systems made in cash as is generally done, tend to be impractical because they must be provided in various nominal terms. Even the existence of cash becomes a burden on the Central Bank to print and control its circulation. With the ease of doing transactions offered through the use of APMK (Card-Based Payment Instruments), Credit Cards are one of the people's choices in transactions, which shows the development in the number of users. However, since the Covid-19 pandemic, the development of the number of credit card users has shown a decline. This study aims to see how the influence of advertising strategies, sales promotions and personal selling on the decision to use credit cards on customers of PT.BNI (Persero) Tbk Manado Region. The analytical tool used is multiple regressions with the help of SPSS 26 application. The results show that the advertising strategy variable, sales promotion variable, and personal selling have a positive and significant impact on Credit Card Usage Decisions for Customers of PT. BNI (Persero) Tbk Manado Region.